Why do financial inclusion policies fail in mobilizing savings from the poor? Lessons from rural south India. (15th November 2017) - Goedecke, Jann; Guérin, Isabelle; D'Espallier, Bert; Venkatasubramanian, Govindan
Abstract: Combining multivariate and qualitative analyses, this micro‐level study suggests an explanation for the persistence of informal savings in rural south India despite publicly run large‐scale programmes to promote bank savings. Gold, in particular, but also Rotating Saving and Credit Associations (ROSCAs) and private lending, remain the dominant forms of savings. We argue that cultural norms and social institutions, such as social class and caste, shape the nature of savings, and also the propensity and opportunities to save. Gold serves multiple purposes, financial, economic, socio‐cultural and political. Furthermore, we find that the preference of Dalits (the lowest caste) for gold illustrates a relative emancipation, which contrasts with the persistence of caste‐related prohibitions preventing them investing in other assets, such as land.